EFEKTIVITAS PUPUK ORGANIK CAIR (POC) KULIT BAWANG MERAH DENGAN PENAMBAHAN EM4 DAN AIR CUCIAN BERAS PADA TANAMAN SELEDRI (Apium graviolens L.) SEBAGAI PRODUK KEWIRAUSAHAAN DITINJAU DARI ASPEK PEMASARAN - Indriani; Zainal Potton; Suharman; Burnama Azhari; Cennawati (STKIP Subang, 2026)
This study aimed to determine the effectiveness of combining shallot skin POC with the addition of EM4 and rice washing water on the growth of celery plants, as well as to analyze the marketing feasibility of the resulting POC product through a SWOT analysis. This research employed a mixed methods approach, combining a quantitative experimental method using a one-factor Completely Randomized Design (CRD) consisting of five treatment levels with three replications, namely P0 (plain water + shallot skin), P1 (P0 + EM4), P2 (P0 + rice washing water), P3 (P0 + rice washing water + EM4), and P4 (P0 + double-dose rice washing water + EM4), and a qualitative descriptive approach for the SWOT analysis. The parameters observed included plant height, number of leaves, leaf area, root volume, root length, and fresh weight of the plants, which were analyzed using analysis of variance (ANOVA) followed by Duncan's test. The results showed that the treatment combinations produced varying effects on the growth parameters of celery, with the single addition of rice washing water yielding the highest fresh weight and root volume compared to the other treatments, establishing it as the best treatment. The SWOT analysis of seven farmer respondents revealed that the shallot skin POC product has strengths in its low-cost, agricultural-waste-based raw materials, weaknesses in farmers' limited direct experience with the product, opportunities for marketing through social media and farmer communities, and threats in the form of farmers' doubts regarding its effectiveness compared to chemical fertilizers. Based on these findings, shallot skin POC has the potential to be developed as an environmentally friendly alternative organic fertilizer that is feasible to market to farmers.